ReaxFF and DFT study on the sulfur transformation mechanism during the oxidation process of lignite. (1st October 2016) - Li, Guang-Yue; Wang, Feng; Wang, Jie-Ping; Li, Ying-Ying; Li, An-Qi; Liang, Ying-Hua
Graphical abstract: Highlights: S-transformation mechanisms in the O2 -atomsphere pyrolysis of lignite are simulated by ReaxFF molecular dynamics. The ReaxFF simulation results show good agreements with previous experimental results. Different forms of S atoms transform to each other with sulfur radicals as their intermediates. O2 molecules react with sulfur radicals and transform them to S-containing gases. Abstract: Two structural models for lignite and O2 -lignite systems were constructed to investigate the impact of O2 atmosphere on the sulfur transformation in the lignite oxidation process. Reactive force field molecular dynamics was employed to simulate the reaction process of the two models at 1000–2000 K, and then the obtained reaction pathways were further confirmed by density functional theory. By analyzing simulation trajectories with C++ program, we have obtained the existing forms, distributions and elementary reactions of sulfur during the pyrolysis and oxidation processes. Different forms of sulfur transform into each other through sulfur radical intermediates in the pyrolysis process. The added O2 molecules or the oxides produced by O2 can react with sulfur radicals, forming sulfur oxide radical intermediates (such as R–S–O and R–S–C–O ). The sulfur atoms in these intermediates transform into small sulfur-containing gas molecules. Thus, sulfur atoms in lignite are finally removed by O2 molecules during the oxidation process.